Understanding the Complex Milieu of Epithelial-Mesenchymal Transition in Cancer Metastasis: New Insight Into the Roles of Transcription Factors - Imodoye, Sikiru O.; Adedokun, Kamoru A.; Muhammed, Abdurrasheed Ola; Bello, Ibrahim O.; Muhibi, Musa A.; Oduola, Taofeeq; Oyenike, Musiliu A. (Frontiers in Oncology, 2021)
Epithelial-mesenchymal transition (EMT) is a physiological program during which polarised, immobile epithelial cells lose connection with their neighbours and are converted to migratory mesenchymal phenotype. Mechanistically, EMT occurs via a series of genetic and cellular events leading to the repression of epithelial-associated markers and upregulation of mesenchymal-associated markers. EMT is very crucial for many biological processes such as embryogenesis and ontogenesis during human development, and again it plays a significant role in wound healing during a programmed replacement of the damaged tissues. However, this process is often hijacked in pathological conditions such as tumour metastasis, which constitutes the most significant drawback in the fight against cancer, accounting for about 90% of cancer-associated mortality globally. Worse still, metastatic tumours are not only challenging to treat with the available conventional radiotherapy and surgical interventions but also resistant to several cytotoxic agents during treatment, owing to their anatomically diffuse localisation in the body system. As the quest to find an effective method of addressing metastasis in cancer intervention heightens, understanding the molecular interplay involving the signalling pathways, downstream effectors, and their interactions with the EMT would be an important requisite while the challenges of metastasis continue to punctuate. Unfortunately, the molecular underpinnings that govern this process remain to be completely illuminated. However, it is becoming increasingly clear that EMT, which initiates every episode of metastasis, significantly requires some master regulators called EMT transcription factors (EMT-TFs). Thus, this review critically examines the roles of TFs as drivers of molecular rewiring that lead to tumour initiation, progression, EMT, metastasis, and colonisation. In addition, it discusses the interaction of various signalling molecules and effector proteins with these factors. It also provides insight into promising therapeutic targets that may inhibit the metastatic process to overcome the limitation of “undruggable” cancer targets in therapeutic design and upturn the current spate of drug resistance. More so, it extends the discussion from the basic understanding of the EMT binary switch model, and ultimately unveiling the E/M cellular plasticity along a phenotypic spectrum via multiple trans-differentiations. It wraps up on how this knowledge update shapes the diagnostic and clinical approaches that may demand a potential shift in investigative paradigm using novel technologies such as single-cell analyses to improve overall patient survival.